A CRITICAL REVIEW ON GUGGULU [COMMIPHORA WIGHTII (ARN.) BHAND.] & ITS MIRACULOUS MEDICINAL USES - Singh, D.C.; Dhyani, Srishti; Kaur, Gagandeep (International Journal of Ayurveda and Pharma Research, 2015)
Guggulu has been a key component in ancient Indian Ayurvedic system of medicine. It has been used extensively by Ayurvedic physicians for centuries to treat a wide variety of disorders, besides its use in pharmaceutical and perfumery industries. Guggulu is a gum or resin extracted from the plant Commiphora wightii (Arn.) Bhand. (Syn. Commiphora mukul Hook. ex. Stocks) or Guggulu tree. Guggulu is a shrub or small tree belonging to Burseraceae family. Guggulu contains volatile oil, gum resin, gugulipids, guggulsterones, guggulsterols, mukolol and other steroids. Guggulu is very much used in Ayuvedic system of medicine as astringent, anti-septic, expectorant, aphrodisiac, carminative, anti-spasmodic, emmenagogue. In Ayurveda, Guggulu is the best among herbs that are used for Medoroga and Vata disorders. It is widely used for obesity and it is also known as fat burning agent all over the world. It helps to lower cholesterol and triglycerides level. Guggulu is very effective in rheumatoid arthritis, gout and sciatica. It is also one of the most important Rasayana of Ayurveda. In addition it treats sluggish liver, stimulates libido, nervous diseases, bronchial congestion, cardiac and circulatory problems, weak digestion, wounds, abscess, foetid ear, fractures, gynaecological problems and various skin diseases. Guggulu is a very important and trustworthy herb in Ayurvedic medicine. Basically it is used almost in every kind of illness due to its amazing treating power. This review is an attempt to describe the pharmacological activities of Guggulu and variable uses of Guggulu in several diseases.